Chronic Exposure to the Combination of Cigarette Smoke and Morphine Decreases CD4+ Regulatory T Cell Numbers by Reprogramming the Treg Cell Transcriptome - Shao, Ying; Cornwell, William; Xu, Keman; Kirchhoff, Aaron; Saasoud, Fatma; Lu, Yifan; Jiang, Xiaohua; Criner, Gerard J.; Wang, Hong; Rogers, Thomas J.; Yang, Xiaofeng (Frontiers in Immunology, 2022)
There is a high incidence of tobacco use among intravenous opioid drug users. It is well established that opioids and tobacco smoke induce a degree of immune activation, and recent work suggests that the combination of these drugs promotes further activation of the immune system. Our approach involved the treatment of wild-type mice with cigarette smoke (SM) for a period of eight weeks, and the chronic continuous administration of morphine (M) via mini-pumps for the final four weeks. In an effort to examine the responses of CD4+CD25highCD127low regulatory T (Treg) cells, the major immune suppressive cell type, to the combined chronic administration of SM and M, we determined the frequency of these cells in the spleen, lymph nodes and lungs. Flow cytometric analyses showed that SM and M individually, and the combination (SM + M) have differential effects on the numbers of Treg in the spleen, lymph node, and lung. Either SM or M alone increased Treg cell numbers in the spleen, but SM+M did not. Furthermore, SM + M decreased Treg cell numbers in the lymph node and lung. We then performed RNA-Seq on Treg cells from mice treated with SM, M, or SM + M, and we found that the S + M induced a number of significant changes in the transcriptome, that were not as apparent following treatment with either SM or M alone. This included an activation of TWEAK, PI3K/AKT and OXPHOS pathways and a shift to Th17 immunity. Our results have provided novel insights on tissue Treg cell changes which we suggest are the result of transcriptomic reprogramming induced by SM, M, and SM + M, respectively. We believe these results may lead to the identification of novel therapeutic targets for suppressing smoke and opioid induced Treg cell impairment.